A Look at the Identification of Managerial Competencies - Hernández Magaña, Jacqueline (2023)
The present investigation aims to identify managerial competencies by applying the performance evaluation model to high-tech companies. The investigation is based on a quantitative and qualitative analysis: the use of the qualitative method affords insight on workers’ perceptions and their appreciation of the company’s management and direction, while the quantitative method contributes to an analysis of data obtained from the aforementioned tools, supported by annual managerial performance results, worker surveys to which experts’ classification of managerial competencies are applied and surveys on managerial quality conducted on both segments: managers and workers. The results show a ratio between the three managerial competencies: strategic competencies, internal organization competencies and personal efficiency, where strategic competencies are prevalent.